2016
DOI: 10.1063/1.4950737
|View full text |Cite
|
Sign up to set email alerts
|

Linear chirped slope profile for spatial calibration in slope measuring deflectometry

Abstract: Slope measuring deflectometry is commonly used by the X-ray optics community to measure the long-spatial-wavelength surface figure error of optical components dedicated to guide and focus X-rays under grazing incidence condition at synchrotron and free electron laser beamlines. The best performing instruments of this kind are capable of absolute accuracy on the level of 30-50 nrad. However, the exact bandwidth of the measurements, determined at the higher spatial frequencies by the instrument’s spatial resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…36 The simple model used here predicts the first zerocrossings at the spatial wavelengths of 1.5 mm and 2.05 mm for the optimal tangential and the standard circular apertures, respectively. However, in publications 25 (see also the results of our measurements in Sec. VIII), it has been shown that with the optimally aligned 2.5-mm circular aperture, 27 the spatial resolution of a NOM-like profilometer is about 1.2 mm if the first zero-crossing of the OTF is assumed as a criterion for the spatial resolution achieved.…”
Section: B Circular Aperturesmentioning
confidence: 71%
See 2 more Smart Citations
“…36 The simple model used here predicts the first zerocrossings at the spatial wavelengths of 1.5 mm and 2.05 mm for the optimal tangential and the standard circular apertures, respectively. However, in publications 25 (see also the results of our measurements in Sec. VIII), it has been shown that with the optimally aligned 2.5-mm circular aperture, 27 the spatial resolution of a NOM-like profilometer is about 1.2 mm if the first zero-crossing of the OTF is assumed as a criterion for the spatial resolution achieved.…”
Section: B Circular Aperturesmentioning
confidence: 71%
“…For the spatial resolution measurement with the OSMS profilometer equipped with different apertures, we use an original test sample with two chirped surface slope patterns 24,25 - Fig. 12.…”
Section: Test Sample With Chirped Profilementioning
confidence: 99%
See 1 more Smart Citation
“…The mirrors with benders were measured and characterized at the BESSY-II Optics Lab at HZB in Berlin. The performance of the bending system and the slope error was measured by means of the BESSY-NOM slope measuring profiler (Siewert et al, 2004) which allows an inspection of the optics for the spatial frequency range between 1.2 mm up to full aperture length (Siewert et al, 2016). A white-light interferometer (WLI) was used to measure the micro-roughness of the mirrors giving an expression for the higher-spatial frequency error which would cause loss of photons because of scatter.…”
Section: Magnet Materialsmentioning
confidence: 99%
“…Such systems can be roughly divided into two types. The first type of pentaprism system contains one scanning pentaprism that directly measures the tilt angles on the surface [6][7][8][9][10][11][12]. This system is sensitive to errors, such as the tilt of the autocollimator, the manufacturing errors of the pentaprism, and the environmental influence.…”
Section: Introductionmentioning
confidence: 99%